Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum

Isolates of alpinia officinarum hance as COX-2 inhibitors: evidence from anti-inflammatory, antioxidant and molecular docking studies - Honmore, Varsha S.; Kandhare, Amit D.; Kadam, Parag P.; Khedkar, Vijay M.; Sarkar, Dhiman; Bodhankar, Subhash L.; Zanwar, Anand A.; Rojatkar, Supada R.; Natu, Arun D. (International Immunopharmacology, 2016)
Background: Inflammation triggered by oxidative stress can cause various ailments, such as cancer, rheumatoid arthritis, asthma, diabetes etc. In the last few years, there has been a renewed interest in studying the antioxidant and anti-inflammatory action of plant constituents such as flavonoids and diarylheptanoids. Aim: To evaluate the antioxidant, anti-inflammatory activity and the total phenolic content of isolated compounds from Alpinia officinarum rhizomes. Furthermore, molecular docking was performed to study the binding mode of these compounds into the active site of cyclooxygenase-2 (COX -2). Methods: A. officinarum rhizomes were extracted by maceration, using methanol. This extract was further fractionated by partitioning with hexane, chloroform and ethyl acetate and these fractions on further purification resulted in isolation of five pure compounds. Characterization was carried out by using H-1 NMR, C-13 NMR and MS. They were further evaluated for antioxidant and anti-inflammatory activity using carrageenan-induced paw edema model in rats. Molecular docking study was performed using Glide module integrated in Schrodinger molecular modeling software. Results: The compounds were identified as 1,7-diphenylhept-4-en-3-one (1), 5-hydroxy-1,7-diphenyl-3-heptanone (2), 3,5,7-trihydroxyflavone (Galangin, 3), 3,5,7-trihydroxy-4'-methoxyflavone (Kaempferide, 4) and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone (5). The compound-3 and compound-5 (10 mg/kg) showed significant (p < 0.001) antioxidant and anti-inflammatory potential. Moreover, total phenolic content was detected as 72.96 mg and 51.18 mg gallic acid equivalent respectively. All the five isolates were found to be good binders with COX-2 (average docking score -9.03). Conclusions: Galangin and 5-hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone exhibited anti-inflammatory and in-vitro antioxidant activity which may be due to presence of phenolic content in it. The molecular docking study revealed that these compounds have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors. The results obtained in this work justify the use of A. officinarum in the treatment of inflammatory disorders like rheumatoid arthritis and inflammatory bowel diseases. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: 5-Hydroxy-7-(4 `'-hydroxy-3 `'-methoxyphenyl)-1-phenyl-3-heptanone; Alpinia officinarum; Anti-inflammatory; Antioxidant; COX-2 inhibitors; Galangin